PENERAPAN RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA PENCURIAN - Heni Marni Bu'ulolo (LPPM Universitas Nias Raya, 2026)
The Indonesian society is accustomed to using deliberate processes to settle conflicts and resolve issues. Customary law, or local Indonesian law, has been utilized since before the Dutch arrived in Indonesia to settle a wide range of conflicts, both civil and criminal, with the goal of reestablishing equilibrium or correcting the situation. Restorative justice is the term now used to address this issue. In criminal cases including the offender, victim, victim's family, and other connected parties, restorative justice emphasizes restoration to the pre-crime state rather than vengeance in an effort to find an equitable conclusion. Finding out how restorative justice is administered to theft crimes is the goal of this research (South Nias Police Research). The study methodology is sociological legal research, which looks at relevant legal provisions in light of societal realities as they exist. The primary, secondary, and tertiary data that were gathered from secondary legal texts were used in the data gathering process. Qualitative data analysis is the method employed. Analyzing qualitative data is done concurrently with the process of gathering data. The best way to resolve a theft case without causing injury to either side is to apply restorative justice, according to the research findings and debate held at the South Nias Police study. While the police must first confirm that the criminal conduct satisfies the legal and material requirements, the implementation of restorative justice is incredibly effective. The police will carry out peace when these two conditions are met by presenting both parties and creating a peace letter signifying that the crime has been finished. that the community, particularly those involved in legal disputes, strongly supports the resolutions reached by the police with the use of restorative justice.